Trypanocidal activity of Brazilian plants against epimastigote forms from Y and Bolivia strains of Trypanosoma cruzi - Alves, Renata Tomé [UNESP]; Regasini, Luis Octávio [UNESP]; Funari, Cristiano Soleo [UNESP]; Young, Maria Cláudia Marx; Rimoldi, Aline; Bolzani, Vanderlan da Silva [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Albuquerque, Sérgio de; Rosa, João Aristeu da [UNESP] (Sociedade Brasileira de Farmacognosia, 2012)
Chagas disease is one of the main public health problems in Latin America. Since the available treatments for this disease are not effective in providing cure, the screening of potential antiprotozoal agents is essential, mainly of those obtained from natural sources. This study aimed to provide an evaluation of the trypanocidal activity of 92 ethanol extracts from species belonging to the families Annonaceae, Apiaceae, Cucurbitaceae, Lamiaceae, Lauraceae, Moraceae, Nyctaginaceae, and Verbenaceae against the Y and Bolivia strains of Trypanosoma cruzi. Additionally, cytotoxic activity on LLCMK2 fibroblasts was evaluated. Both the trypanocidal activity and cytotoxicity were evaluated using the MTT method, in the following concentrations: 500, 350, 250, and 100 µg/mL. Benznidazole was used for positive control. The best results among the 92 samples evaluated were obtained with ethanol extracts of Ocotea paranapiacabensis (Am93) and Aegiphila lhotzkiana (Am160). Am93 showed trypanocidal activity against epimastigote forms of the Bolivia strain and was moderately toxic to LLCMK2 cells, its Selectivity Index (SI) being 14.56, while Am160 showed moderate trypanocidal activity against the Bolivia strain and moderate toxicicity, its SI being equal to 1.15. The screening of Brazilian plants has indicated the potential effect of ethanol extracts obtained from Ocotea paranapiacabensis and Aegiphila lhotzkiana against Chagas disease.
Keywords: biodiversity; Chagas; cytotoxicity; disease; strains; trypanocidal activity; Trypanosoma cruzi